Role of Interventional Radiology in Children with Biliary and Gallbladder Diseases - Yakupovich, Anel; Rajeswaran, Shankar; Green, Jared; Donaldson, James S. (Seminars in Interventional Radiology, 2021)
Biliary and gallbladder diseases in infants and children often present unique diagnostic and therapeutic challenges that require a fundamental understanding of notable biliary diseases and anatomical variations. Surgical and endoscopic approaches that are often the gold standard in adult biliary treatment may be technically challenging and are associated with a high morbidity that may warrant a multidisciplinary treatment approach. This article will provide a comprehensive overview of the biliary conditions where interventional radiology can play a vital role in the diagnosis, management, and treatment. Differences in approach or technique between children and adults will be highlighted.
Keywords: percutaneous cholecystostomy; percutaneous transhepatic cholangiography; pediatric population